Conwy Castle
The success of the Crown in subjugating Wales changed the balance of English politics in favor of the King, and the building of royal castles continued whenever order was threatened. Their construction, representing as great an effort as that of cathedral building, continued into the next century. Beaumaris Castle, just across the water from Conway, employed 400 masons, 1,000 laborers, 200 carters, and 30 carpenters and smiths when work was at its height, comparable with civil engineering works today.